Do Performance Assessment has Contribution to Achieve Students’ Commnunication Skills? - Aisah Isnaeni; A Ratna Wulan; R Solihat (Universitas Sebelas Maret, 2017)
Communication skill was an important component of education. This study aims to analyzed students' communication skills and response by using performance assessment on water cycle concept. The method that used in this study is descriptive. Subject consists of first-grade students’ in senior high school (n:32). The instruments that used in this study are the task, observation sheets, questionnaire, self and peer assessment. Those instruments analyzed four indicators of communication such as; (1) articulate thoughts and ideas effectively,(2) listen effectively, (3) use communication for a range of purposes and (4) Communicate Effectively in diverse environments. Sccorring of instruments has two categories, score from 1-4 for task and sheets of observation, score from 0 and 1 for self and peer assessment and questionnaire using descriptive analyzed. Then, indicators of communication skills categorized into three groups: high, medium and low. The data showed that all of the indicators in medium categorized 81.3% in the first indicator, 53.1% in the second indicator, 46.9% in the third indicator, and 68.8% in the fourth indicator. Therefore students’ have communication skill in medium category and most of the students’ has positive respond in performance assessment because its’ can help students’ to fix their performance in the instructional process.